2016
DOI: 10.3389/fmicb.2016.01367
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Dynamics of Pacific Oyster Hemolymph Microbiota across Multiple Scales

Abstract: Unveiling the factors and processes that shape the dynamics of host associated microbial communities (microbiota) under natural conditions is an important part of understanding and predicting an organism's response to a changing environment. The microbiota is shaped by host (i.e., genetic) factors as well as by the biotic and abiotic environment. Studying natural variation of microbial community composition in multiple host genetic backgrounds across spatial as well as temporal scales represents a means to unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
101
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(111 citation statements)
references
References 117 publications
(192 reference statements)
9
101
1
Order By: Relevance
“…The compositions of the microbiomes of our focal hosts, as measured by Bray–Curtis and Jaccard indices, do vary significantly across PtC, which is consistent with results from other marine invertebrates including corals (Lema et al ., ; Pantos et al ., ; Kellogg et al ., ) and some sponges (Burgsdorf et al ., ) analysed across various dispersal barriers or large geographic distances. In our case, such differentiation is largely driven by composition of rare taxa and changes in the relative abundance of dominant taxa at each site, as has been seen previously in oyster hemolymph microbiomes (Lokmer et al ., ). This is exemplified by PERMANOVA results of the binary Jaccard distances (Table ) and lack of change in hierarchical clustering between the whole dataset and the 100% core microbiome in L. gigantea and C. funebralis (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compositions of the microbiomes of our focal hosts, as measured by Bray–Curtis and Jaccard indices, do vary significantly across PtC, which is consistent with results from other marine invertebrates including corals (Lema et al ., ; Pantos et al ., ; Kellogg et al ., ) and some sponges (Burgsdorf et al ., ) analysed across various dispersal barriers or large geographic distances. In our case, such differentiation is largely driven by composition of rare taxa and changes in the relative abundance of dominant taxa at each site, as has been seen previously in oyster hemolymph microbiomes (Lokmer et al ., ). This is exemplified by PERMANOVA results of the binary Jaccard distances (Table ) and lack of change in hierarchical clustering between the whole dataset and the 100% core microbiome in L. gigantea and C. funebralis (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Marine molluscs are one of the most diverse and ecologically important groups of marine invertebrates, with many species providing a variety of ecosystem services including supporting commercial and artisanal fisheries. Information about the diversity and compositions of microbes associated with molluscan hosts still remains scarce, although microbiomes of some bivalve (Prieur et al, 1990;Betcher et al, 2012;King et al, 2012;Lokmer et al, 2016;Pierce et al, 2016;Arfken et al, 2017) and gastropod (Dudek et al, 2014;Zbinden et al, 2014;Aronson et al, 2017;Cicala et al, 2018) species have been quantified. Moreover, existing analyses of marine gastropod microbiomes have primarily focused on the digestive tract, with only one study including gillspecific microbiome data (Zbinden et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Considering 16S rRNA gene studies, the choice of hypervariable region of 16S rRNA gene on determining the phylogenetic resolution cannot be overlooked (Tremblay et al 2015;Yang et al 2016). Studies that involve high-throughput sequencing of V1-V2 region (haemolymph) (Lokmer et al 2016b), V3-V4 region (gill) (Wegner et al 2013), V3-V5 region (gut) (Trabal Fern andez et al 2014) and V6 region (haemolymph and digestive gland) (Vezzulli et al 2018) of the 16S rRNA gene also reported the dominance of phylum Proteobacteria. However, at a higher resolution, Wegner et al (2013) It should also be noted that the above studies have used different nucleic acid extraction kits compared to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…unculturable bacteria) may go undetected using these methods (Garnier et al, 2007). More recently, 16S rRNA gene-based analysis of the microbial diversity, based on next-generation sequencing protocols, was employed for taxonomic identification of bivalve-associated bacteria (Lokmer and Wegner, 2015;Lokmer et al, 2016). However, although this approach allows us to overcome the cultivation bias, 16S rRNA profiling could not be successfully applied for high taxonomic resolution analysis of the microbial community (e.g.…”
Section: Introductionmentioning
confidence: 99%